Benefits management in software development: A systematic review of empirical studies - Knut Kjetil Holgeid; Magne Jørgensen; Dag I. K. Sjøberg; John Krogstie (IET Software)
Abstract Considerable resources are wasted on software projects delivering less than the planned benefits. Herein, the objective is to synthesize empirical evidence of the adoption and impact of benefits management (BM) in software development, and to suggest directions for future research. A systematic review of the literature is performed and identified 4836 scientific papers of which the authors found 47 to include relevant research. While most organizations identify and structure benefits at the outset of a project, fewer organizations report implementing BM as a continuous process throughout the project lifecycle. Empirical evidence gives support for positive impact on project outcome from the following BM practices: identifying and structuring benefits, planning benefits realization, BM during project execution, benefits evaluation and the practice of having people responsible for benefits realization. The authors suggest four research directions to understand (1) why BM practices sometimes not are adopted, (2) BM in relation to other management practices, (3) BM in agile software development and (4) BM in the context of organizations' value creation logics.